Perancangan Home Security System Berbasis Arduino Uno Menggunakan Simulasi Proteus - Slamet Nurhidayat; Mulia Agustiani; Sri Muzzayanah; Ulinnuha Latifa (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2022)
The rise in population has resulted in increased development in big cities. It causes disturbance and insecurity from various aspects, including fire, crime and electricity problems which usually occur in densely populated houses in big cities. This study aims to design a home security system from these three aspects. The methods used in designing this Arduino UNO-based system are performing a simulation design on the Proteus Software to design and simulate the circuit and making a prototype design on the hardware implementation, the test results of which are then analyzed. This series of home security systems use MQ-2 and DS18B20 sensors as fire detectors, HC-SR501 as a motion detector for crime indications and a current sensor as an overcurrent detector with buzzer, led and relay outputs. The test results of the two designs show that the system can run smoothly and function according to the input given and the design can be implemented using hardware and be developed sustainably.